Individual magnitudes of neural variability quenching are associated with motion perception abilities - Daniel, Edan; Dinstein, Ilan (Journal of neurophysiology, 2021)
The current study demonstrates that better visual perception abilities in a motion discrimination task are associated with larger quenching of neural variability. In line with previous studies and signal detection theory principles, these findings support the hypothesis that cortical sensory neurons increase reproducibility to enhance detection and discrimination of sensory stimuli. Remarkable trial-by-trial variability is apparent in cortical responses to repeating stimulus presentations. This neural variability across trials is relatively high before stimulus presentation and then reduced (i.e., quenched) ∼0.2 s after stimulus presentation. Individual subjects exhibit different magnitudes of variability quenching, and previous work from our lab has revealed that individuals with larger variability quenching exhibit lower (i.e., better) perceptual thresholds in a contrast discrimination task. Here, we examined whether similar findings were also apparent in a motion detection task, which is processed by distinct neural populations in the visual system. We recorded EEG data from 35 adult subjects as they detected the direction of coherent motion in random dot kinematograms. The results demonstrated that individual magnitudes of variability quenching were significantly correlated with coherent motion thresholds, particularly when presenting stimuli with low dot densities, where coherent motion was more difficult to detect. These findings provide consistent support for the hypothesis that larger magnitudes of neural variability quenching are associated with better perceptual abilities in multiple visual domain tasks. NEW & NOTEWORTHY The current study demonstrates that better visual perception abilities in a motion discrimination task are associated with larger quenching of neural variability. In line with previous studies and signal detection theory principles, these findings support the hypothesis that cortical sensory neurons increase reproducibility to enhance detection and discrimination of sensory stimuli.